Understanding Consequences and Tradeoffs of Melt Processing as a Pretreatment for Enzymatic Depolymerization of Poly(ethylene terephthalate). Issue 13 (31st March 2022) - Chang, Allen C.; Patel, Akanksha; Perry, Sarah; Soong, Yahue V.; Ayafor, Christian; Wong, Hsi‐Wu; Xie, Dongming; Sobkowicz, Margaret J.
Abstract: Melt extrusion pretreatment of poly(ethylene terephthalate) (PET) prior to enzymatic depolymerization with an unpurified leaf branch compost cutinase enzyme cocktail is explored to ascertain the efficiency gained by different processing methods on the enzymatic depolymerization of PET. Specific surface area (SSA) is investigated as a key factor in reducing depolymerization time. Higher SSA substrates (>5.6 mm 2  mg −1 ) show higher depolymerization rates (≈0.88 g L −1 terephthalic acid [TPA] per day) and no induction phase, while lower SSA substrates (≈4.3, 4.4, and 5.6 mm 2  mg −1 ) show, after an initial induction phase, similar depolymerization rates (≈0.46, 0.45, and 0.44 g L −1 TPA per day) despite increases in SSA of up to 30%. The mechanism of enzymatic depolymerization manifests in the appearance of anisotropic pitting. Longer incubation time used to overcome the induction phase in low SSA substrates allows for nearly full recovery of monomeric products, but manual pregrinding of extruded PET sharply increases SSA, depolymerization rate, and substrate crystallinity which may decrease the maximum recycled yield of the product materials. An estimate of the energy cost of increasing SSA is made and its effects on material properties are discussed. This work highlights key material structure and pretreatment aspects influencing the enzymatic recycling of PET. Abstract : Postconsumer poly(ethylene terephthalate) (PET) bottle flake modified via extrusion is enzymatically depolymerized to produce monomers of terephthalic acid. Improvements in this process are gained by changing substrate properties instead of enzyme properties. A twofold increase in depolymerization rate can be achieved just by changing a substrate's specific surface area.